تأثير الاختلاف الكمي في احتياجات مياه الري العادية والممغنطة على محصول الذرة - سلامة معن; الجودي حسان (Latakia University Journal -Engineering Sciences Series, 2019)
تهدف الدراسة إلى تحديد تأثيرات الاختلاف الكمي في أثناء استخدام مياه ري عادية ومياه ري ممغنطة لتغطية الاحتياج المائي لمحصول الذرة الصفراء. تضمنت التجربة ست معاملات مختلفة, ثلاث منها لماء الري الممغنط, والثلاث الأخرى لماء الري العادي. تمت زراعة ست مساكب مساحة الواحدة 2.64 م2 بحبوب الذرة وتم تقييم إنتاجية كل معاملة من الحبوب والعلف بالطريقة الوزنية (كغ/دونم) كما تم حساب الاستهلاك المائي (لتر/1كغ مادة صلبة). وقد أعطت التجربة إشاراتٍ واضحةً على قدرة مياه الري الممغنطة على زيادة الإنتاجية لمحصول الذرة كحبوب مقارنة بمياه الري العادية, كما أشارت إلى قدرتها على توفير الماء لتشكيل الحبوب مقارنة بمعاملات الماء العادي أيضاً. The study seeks to determine the effects of the quantitative difference during applying normal and magnetized irrigation water to cover the water needs of the maize crop. The experiment has included six different coefficients, three of which are for the magnetized irrigation water, the others for normal water irrigation. Six terraces have been planted with maize grains. Having finished, the productivity has been estimated by means of the weight method. Water consumption has also been calculated. The experiment has given notable references about the ability of the magnetized irrigation water to increase the productivity of the maize crop as grains comparing with the normal one, and has indicated its ability to save water to form grains compared with normal water coefficients.